Unity in Diversity : A Study of Schools of Islamic Jurisprudence - Abdul Hameed Badmas Yusuf; Ismail Danjuma Yusuf (Indonesian Journal of Law and Islamic Law (IJLIL), 2025)
Islamic jurisprudence (Fiqh) is human understanding of Islamic law (Shari’ah) which is divine in nature. As major sources of Islamic law, both Qur’an and Sunnah address fundamental issues, leaving out detailed matters for human interventions to decide on in the light of general principles generated from the primary sources. This paves the way for Ijtih?d as an intellectual process undertaken by a master-jurist (mujtahid) who derives legal rules from the sources of Islamic law. Thus, the emergence of different schools of Islamic thought a natural outcome of Ijtih?dat (pl. Ijtih?d) of leading jurists of major schools of thought. All the schools of Islamic jurisprudence, especially the four dominant ones, employed distinct principles which appear mutually antagonistic. Yet, beneath these diverse principles is uncompromising unity of sources and purpose. This paper seeks to study juristic principles of the four famous schools of Islamic jurisprudence, namely Hanafi, Maliki, Shafi’i, and Hanbali Schools of legal thoughts. It employs a doctrinal research method, alongside inductive and analytical methods. The paper finds that despite their divergent positions on different legal issues, the eponyms of these schools of thought were united in many respects: they subscribed to the same primary sources, discouraged dogmatism (Taqlid), and charged their disciples to evaluate their opinions against the primary sources of the Shari’ah. Above all, it was obvious that each of those pious jurists was driven by sincerity of purpose and the desire to unravel the legal rule of Islamic law. In essence, this is unity in diversity.